Integrating Financial Therapy within Family-Owned Businesses: A Theoretical Case Vignette with Recommended Strategies for Consulting with Copreneurs - Josh W Harris; Rob Stephens; Derek Sensenig; Stefanie Pickard; Megan A McCoy; Richard Kahler (Journal of Financial Therapy, 2020)
Broadly speaking, finances are often one of the most strenuous aspects of a relationship. One potential contributing factor to financial conflict experienced by couples are having different beliefs or attitudes towards money, coined previously as money scripts (Klontz, Kahler, & Klontz, 2008). Differing money scripts between partners can cause a breach in understanding of their partner's internal experience around money that may lead to misunderstanding and conflict. This may be magnified for copreneurs, or romantic partners, who integrate a personal and working relationship within a business’s ownership structure. In this unique arrangement of personal and professional relationships, the traditional lines separating work and home life are either nonexistent or blurred. This paper serves to explore the conflict through a hypothetical case study and provides detailed financial therapy interventions that may be used to help copreneurs who are experiencing money conflict. The outline of interventions serves to aid financial therapists in their work with clients who are part of a family-owned business by helping these clients better communicate through the unique dynamics of a copreneur relationship.
Keywords: copreneurs; money scripts; financial therapy; case vignette